Health related behaviour changes in pregnant women during COVID-19 pandemic - Dutta, Indrani; Usha Madhulika Horo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy associated anxiety and depression is very well known for its prevalence. Pandemic like COVID-19 all the more is additive to the levels of anxiety and depression during pregnancy, especially for mothers who are concerned about feto-maternal wellbeing. This study makes an effort to analyze the health-related behavior changes and psychological impact of pregnant women after COVID-19 outbreak. Methods: Cross sectional, questionnaire-based study conducted on pregnant ladies visiting labor room and out-patients department RIMS, Ranchi from April 2020 to September 2020. Results: Most patients were primigravida and turned up only in third trimester. Pregnancy complications like heart disease, GDM, jaundice, PIH were present in 28% of participants. 48% participants had no family income during pandemic. The 92% women wore masks, 80% practiced social distancing, 72% practiced frequent handwashing, 72% practiced frequent handwashing during pandemic, 80% had no regular antenatal check-up. Almost 64% participants showed mild to moderate anxiety, 34% had moderate depression and 40% had moderate stress. Four percentages had severe anxiety, 2% had severe depression and 12% had severe stress. Usage of mask was inversely related to GAD7 scores, but had no correlation with EPDS scores. Rest parameters like frequent handwashing, social distancing, stressful behavior, not going out and frequent handwashing were directly related to GAD 7 and EPDS score. Conclusions: Mental health and preventive behavior of respondents could be attributed to socio demographic, social, situational, economic status, family conditions and perception of severity of Covid19.